Cervical Collar versus Manual Traction in Patients with Mechanical Neck Pain - Abd El Rahim, Ahmed Assem; M. Essa, Mohamed; Shabana, agdy M.A.; Elhakk, Sahar M (International Journal of Psychosocial Rehabilitation, 2020)
Background: Mechanical neck pain is very common major public health problem in all countries. Purposes: Was to investigate the effect of manual traction, and cervical collar on mechanical neck pain and functional disability. Subjects: Sixty mechanical neck pain patients aged from 20-35 years of both sexes, randomly divided into three groups, selected from Deraya University outpatient clinic. Methods: Group (A): 20 patients received cervical collar in addition to traditional physical therapy. Group (B): 20 patients received manual traction in addition to traditional physical therapy, while group (C) of 20 patients received traditional physical therapy. The treatment was applied for four weeks, three sessions per week. Pain and disability were measured by McGill Pain Questionnaire, and neck disability index. Cervical flexion, extension ROM was measured by electronic digital goniometer before and after the treatment. Results: There was a statistically significant decrease in pain, and disability in group (B) than other groups with a rate of change by 84.48%, and 73.45% respectively. There was a statistically significant increase in flexion and extension ROMs in group (B) than other groups with a rate of change 57.82%, and 76.2% respectively. Conclusion: Manual traction and cervical collar in addition to traditional physical therapy can be used as an effective treatment in patients with mechanical neck pain but manual traction superior than cervical collar